Knowledge, attitudes, and conservation challenges for the Lesser Adjutant in Nepal - Hem Bahadur Katuwal; Hari Prasad Sharma; Prashant Rokka; Nitesh Kumar Das; Rui-Chang Quan (Global Ecology and Conservation, 2024)
The knowledge and attitudes of local communities are essential for understanding the distribution, ecology, and pertinent threats to bird species, particularly those existing beyond protected areas. Despite the reliance of large waterbirds like storks on human-dominated landscapes, research in this domain is limited across its range. To address this knowledge gap, we conducted semi-structured interviews with 546 local people across seven districts in the lowlands of Nepal from 2021 to 2022 to insights into people’s knowledge, attitudes, and the conservation challenges faced by the Lesser Adjutant (Leptoptilos javanicus). Our findings showed that people possessed substantial knowledge about the species name and ecology. A majority of the people (89%), agreed with the statement that the Lesser Adjutant contributes to ecosystem services in farmlands, whereas they disagreed with the notions that it is a pest, unattractive species, or possess medicinal values, with 84%, 82%, and 67% respectively holding these views. In addition, 65% of people reported a significant decline in its population, with 67% noting a decrease in distribution range and 49% observing a decline in nesting sites over the past decade, primarily due to food scarcity, habitat loss, the felling of nesting trees, wetland degradation, pesticide use, and hunting, among other factors. A striking knowledge gap was evident, with approximately two-thirds of people unaware of its conservation status, and over 80% highlighting the absence of local awareness initiatives. Nonetheless, majority of the people (95%) expressed strong support for its conservation, emphasizing the need for intensified awareness programs, habitat conservation and management, and the protection of large trees, among other measures, to ensure the well-being of this iconic species beyond the confines of protected areas. Our study provides essential baseline data for researchers and conservation managers to design effective plans and policies for the research and conservation of the Lesser Adjutant.